From trainee to general practitioner: A qualitative study of transition experiences of Flemish GP trainees - Ellen Tisseghem; Joke Fleer; Melissa Horlait; Peter Pype; Emelien Lauwerier (European Journal of General Practice)
Background The transition from trainee to professional marks a key milestone in a family doctor’s career, bringing both emotional and mental challenges. This critical period of specialisation shapes how young doctors adapt and influences their future career choices.Objectives We explored trainees’ experiences during their first year of advanced medical training in family medicine/general practice, including barriers and facilitators.Methods Using qualitative methodology, we conducted ten focus group interviews with 111 trainees. These group interviews were held as part of small-group sessions integrated into a self-guided reflection course. All interviews were held between February 2021 and March 2021, conducted online via MS Teams, recorded, and transcribed verbatim for analysis.Findings Our analysis uncovered two adaptational processes during this transition period: personal adaptation and professional socialisation. We interpreted this as a complex balancing act, with impact on mental health aspects such as energy, exhaustion, and self-confidence. Multiple elements at different levels influenced these processes, including the workplace (e.g. interactions with colleagues and patients), the educational program (e.g. assignments, courses), and societal expectations (e.g. role expectations, support).Conclusion The findings highlight the importance of understanding both personal adaptation and professional socialisation to support trainees effectively during their transition into practice. Future studies should validate these findings and explore their evolution over time, particularly in relation to adaptation and career choices.